Investor inattention, firm reaction, and Friday earning announcements - Della Vigna, Stefano 1973-; Pollet, Joshua M. (National Bureau of Economic Research, 2005)
Do firms release news strategically in response to investor inattention? We consider news about earnings and analyze the response of returns to announcements on Friday and other weekdays. Friday announcements have less immediate and more delayed stock return response. The delayed response as a percentage of the total response is 60 percent on Friday and 40 percent on other weekdays. In addition, abnormal trading volume around announcement day is 10 percent lower for Friday announcements. These findings suggest that weekends distract investor attention temporarily. They support explanations of post-earning announcement drift based on underreaction to information caused by limited attention. We also document that firms release worse announcements on Friday. Friday announcements are associated with a 45 percent higher probability of a negative earnings surprise and a 50 basis points lower abnormal return. The firm-based evidence of strategic news release corroborates the investor-based evidence of inattention on Friday. The results for stock returns, volume, and strategic behavior support the hypothesis of limited attention.
Keywords: Corporations - Public relations; Stocks - Psychological aspects; Öffentlichkeitsarbeit / Publizitätspflicht / Zeit / Informationsverhalten / Anlageverhalten